Kepatuhan PPh Pasal 23 Pada Lembaga Pendidikan Anak Usia Dini - Marsetya Ringga Dwyandara; Puji Rahayu (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Tax is the main source of state revenue used to finance public services and national development; therefore, tax compliance is a fundamental pillar of fiscal sustainability. Early Childhood Education Institutions (PAUD) play a strategic role not only in human resource development but also as micro-economic units that conduct various commercial transactions, such as catering services, building rentals for events, and cleaning services, which may be subject to Article 23 Income Tax (PPh Article 23). Understanding the obligations related to tax withholding, payment, and reporting is essential to prevent administrative violations and fiscal risks. This study aims to analyze the level of compliance with Article 23 Income Tax withholding, payment, and reporting at PAUD TK X; to identify types of transactions subject to Article 23 Income Tax; and to examine obstacles faced by PAUD management. This research employs a descriptive qualitative method using a case study approach. Data were collected through semi-structured interviews with the PAUD treasurer and supported by secondary data in the form of transaction records, withholding tax slips, and monthly tax returns. The results indicate that PAUD TK X has complied with Article 23 Income Tax regulations, as evidenced by proper withholding at a rate of 2% for service providers with Tax Identification Numbers (NPWP), issuance of electronic withholding tax slips (e-Bupot), timely tax payments through billing codes, and punctual submission of Monthly Tax Returns. Although minor obstacles remain, particularly related to limited human resources and the complexity of the tax administration system, overall compliance is considered high. Continuous assistance and guidance are recommended to maintain sustainable tax compliance in early childhood education institutions.